PEMANFAATAN LIMBAH SERAT KAPAS DARI INDUSTRI PEMINTALAN UNTUK FELT DAN PAPAN SERAT - Eva Novarini (Arena Tekstil, 2018)
Cotton is widely used for clothing material, because it is able to absorb sweat/water, so comfortable to wear. But the product is still an export comodity and waste that occurs after spinning into yarn is about (4 - 5)%. Much of the waste still contains short fibers, potentially as composite reinforcement; and the rest are dirt, dust, soil and others. Therefore, in the framework of handling and utilization of such waste, in order to produce an added value product, then a research was conducted to make biocomposites using that waste. The purpose is to get a biocomposite with a cotton fiber waste of felt (a nonwoven product) with a low melt polyester matrix and manufactured wood in the form of a fiber board with an epoxy resin matrix that can meet applicable standards. From the test results, it is known that the felt can absorb sound up to 78% at the reference frequency of 5000 Hz (meets minimum standards for sound absorbing coefficient, based on ISO 11654: 1997), so it can be used as a sound absorber material (for building/automotive) and can also be used as raw material for automotive textile (door trim, dashboard or head lining).  In addition, the fiber board also has performance that meets the standard (SNI 01-4449-2006) and can reflect sound ≥ 90%, so it can be used as a sound reflector interior panel